2021
DOI: 10.5483/bmbrep.2021.54.6.218
|View full text |Cite
|
Sign up to set email alerts
|

Long-term depletion of cereblon induces mitochondrial dysfunction in cancer cells

Abstract: Cereblon (CRBN) is a multi-functional protein that acts as a substrate receptor of the E3 ligase complex and a molecular chaperone. While CRBN is proposed to function in mitochondria, its specific roles are yet to be established. Here, we showed that knockdown of CRBN triggers oxidative stress and calcium overload in mitochondria, leading to disruption of mitochondrial membrane potential. Notably, long-term CRBN depletion using PROteolysis TArgeting Chimera (PROTAC) induced irreversible mitochondrial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“… 87 Hepatocarcinoma TD-165 VHL and CRBN CRBN Park et al. 88 BETd-260 CRBN BRD4 Zhang et al. 89 PROTAC X-protein VHL X protein Montrose and Krissansen 90 Cholangiocarcinoma ARV-825 CRBN BRDs Lu et al.…”
Section: Application Of Proteolytic Targeting Chimeras In Gastrointes...mentioning
confidence: 99%
See 2 more Smart Citations
“… 87 Hepatocarcinoma TD-165 VHL and CRBN CRBN Park et al. 88 BETd-260 CRBN BRD4 Zhang et al. 89 PROTAC X-protein VHL X protein Montrose and Krissansen 90 Cholangiocarcinoma ARV-825 CRBN BRDs Lu et al.…”
Section: Application Of Proteolytic Targeting Chimeras In Gastrointes...mentioning
confidence: 99%
“…Another study showed that knockdown of CRBN in the hepatoblastoma HepG2 cell line and cervical cancer HeLa cell line resulted in increased ROS production, increased oxidative stress, mitochondrial calcium overload, reduction of mitochondrial membrane potential, increased cytochrome c levels, and superoxide accumulation. 88 Therefore, mitochondria undergo irreversible damage induced by ROS, which ultimately inhibits the proliferation, viability, and cell cycle progression (manifested by an increase in G1 and G2/M phase cells, and a decrease in S phase cells) of HepG2 and HeLa cells, and induces apoptosis. In addition, the levels of apoptotic markers, including caspase3/7, cleaved PARP, cleaved cystathione 7, p53, and p21, were increased in CRBN-knockdown cells.…”
Section: Application Of Proteolytic Targeting Chimeras In Gastrointes...mentioning
confidence: 99%
See 1 more Smart Citation